The δίκη ἐξούλης and the δίκη βιαίων - García Domingo, Enrique (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2017)
The δίκη ἐξούλης and the δίκη βιαίων are two different actions provided for different cases. However, they have not always been properly distinguished. The aim of this article is to defi ne when either procedure is used. We will also address the question of whether the δίκη ἐξούλης is a process πρός τινα ο κατά τινος.
Keywords: Law; Lexicography; Literature.